pH influences the biocompatibility of methylene blue solutions - Gusman, David Jonathan Rodrigues [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Novaes, Vivian Cristina Noronha [UNESP]; Matheus, Henrique Rinaldi [UNESP]; de Araujo, Nathália Januario [UNESP]; de Almeida, Juliano Milanezi [UNESP] (Springer Nature, 2018)
Objective: The aim of this study was to investigate the biocompatibility of methylene blue at different pH levels through the method of implantation in subcutaneous tissue. Materials and methods: Eighty-four sterilized polyethylene tubes were allocated in the subcutaneous tissue of 28 rats, each one receiving four tubes, set into four groups: group tube (G-T)—empty tube, fibrin group (G-F)—tube filled with fibrin sponge, group methylene blue pH 7 (G-MB/pH 7)—tube filled with fibrin sponge soaked by methylene blue (100 μg/ml) at pH 7.0, and group methylene blue pH 1 (G-MB/pH 1)—tube filled with fibrin sponge and soaked by methylene blue (100 μg/ml) at pH 1.0. After 7, 15, and 30 days, seven animals from each group were euthanized, and the tubes involved by the surrounding tissue were removed and fixed with 4% buffered formaldehyde solution. The collected pieces were processed and histological sections (4 μm) were stained with hematoxylin and eosin and analyzed by light microscopy. Scores were assigned to analysis of histopathologic parameters. The results were statistically analyzed by the Kruskal–Wallis test (p ≤ 0.05). Results: At 7 and 30 days, the G-MB/pH 1 group showed no significant difference in the G-T control group, while G-MB/pH 7 had a significant increase on tissue reaction, also when compared to G-T. At 15 days, there was no statistical difference between the groups. Conclusion: Within the limits of this study, it is concluded that methylene blue at pH 1.0 provides better biocompatibility than at pH 7.0.
Keywords: Biocompatibility testing; Hydrogen-ion concentration; Methylene blue; Subcutaneous tissue